Avaliação da funcionalidade familiar por idosos - Vera, Ivana (2013)
Demographic and epidemiologic transitions influence the Family arrangements, making the course of life of the families dynamic and leading to intergenerationality. These factors influence several aspects of the life of the elderly, especially their family relations. To assess the family dynamic of the elderly is associated to the lack of studies on the family function in this context. Thus, the objective was to assess the family relationship of the elderly using the family APGAR and the associated factors in a capital city in the Brazilian Mid-West region. This is a cross-sectional, populationbased, epidemiological study which is part of the matrix study carried out by the Rede de Vigilância a Saúde do Idoso (REVISI -Network for Elderly Health Surveillance). The probability sample was formed by 934 elderly living in the urban area of Goiânia, Goiás, Brazil. Data were collected from November 2009 to April 2010. A standardized questionnaire was applied including socioeconomic and demographic variables, self-referred health conditions, pain, falls, and access to health services. Scales to measure functional and cognitive capacities were applied. Family APGAR index assessed the family dynamics. Scores 7 refer to Good Family Function (GFF) and scores <7 refer to Family Dysfunction (FD). The outcome variables considered were the family relations and all the other relations considered as predictor variables in the instrument. For univariate association analysis, Chisquare (c)2, or Fischer’s Exact test was used at a 5% significance level. The association magnitude was expressed by Prevalence Ratio (PR) and their respective confidence intervals (CI95%). Multiple logistic regressions were used to identify factors associated to the outcome by building the model with the predictor variables whose p values were 0.20 in the univariate analysis. When we inquired the total sample that answered the index, GFF was associated to age, education, having an income, self-refer health as bad /terrible, pain complaint osteoporosis and cancer. As for the elderly who referred family dysfunction, high dysfunction was associated to falls, and a previous episode of AMI. When the population aged 80 was assessed, GFF was associated to variables of referring bad /terrible health, osteoporosis and falls. These results characterize the family dynamics of non-institutionalized elderly regarding GFF prevalence and they point to the need to adjust the current State policies to focus on the real needs of this population stratum so that professionals understand and can help balance the family dynamics and that it can strengthen the health team that works on strategies for Family health.